Using physiological biomarkers in forensic psychiatry: a scoping review - Mens, Jenthe; Masthoff, Erik; Bogaerts, Stefan; Heus, Pauline (Frontiers in Psychiatry, 2025)
Forensic psychiatry aims to reduce criminogenic risks and enhance societal safety. While effective at a macro level, crime recidivism rates among forensic patients remain substantial. This underlines the need for innovation, with growing interest in the use of physiological biomarkers. To identify the extent (size), range, (variety), and nature (characteristics) of evidence on the use of physiological biomarkers in forensic psychiatry, a systematic scoping review was conducted following JBI methodology and PRISMA-ScR guidance. Data on study characteristics and results were extracted by two independent reviewers from 431 primary research studies published in scientific journals and dissertations. Most studies were conducted in North America (53.4%) and Europe (41.3%). The majority employed an observational design (95.6%) and were cross-sectional (87.7%). Studies predominantly focused on males (84.9%) and adults (85.9%). The most common diagnoses were psychopathy/antisocial personality disorder (51.7%) and sexual disorders (21.8%). Brain activity served as a biomarker outcome in 51.3% of studies, followed by peripheral sympathetic arousal (29.2%) and peripheral sexual arousal (13.8%). Biomarker assessment methods reflected these findings. Etiologic biomarker functions were most common (77.2%), followed by diagnostic functions (12.7%). Findings reveal several gaps in the existing scientific literature. Specifically, more experimental and longitudinal research is needed to integrate physiological biomarkers into e.g., interventions, effect monitoring, and (risk) assessment. Also, a greater focus on juveniles, patients with psychotic and substance use disorders, and the use of newer biomarker assessment methods measuring peripheral arousal is essential to advance the field.Systematic review registrationhttps://osf.io/, 10.17605/OSF.IO/46QBU.